Dynamics and Uncertainty in Land Use Conversion for Perennial Energy Crop Production: Exploring Effects of Payments for Ecosystem Services Policies. (August 2019) - Li, Xiaogu; Zipp, Katherine Y.
Abstract : Perennial energy crops like switchgrass that are used for biofuel production have the potential to generate various water quality benefits such as reduced nitrogen runoff. Yet the current expected returns to switchgrass are not profitable enough for these crops to be widely adopted by U.S. farmers due to relatively unstable yields, volatile revenues, and high costs of crop establishment. This study uses a dynamic economic model to investigate the uncertainties in the yields and costs of switchgrass production, in comparison with those of corn-soybeans in the Chesapeake Bay Watershed in Pennsylvania. Results indicate that farmers would be willing to convert corn-soybeans to switchgrass land use with the provision of payments for ecosystem services (PES). A targeted PES policy based on the environmental effectiveness of the crop land is found to be slightly more effective in providing nitrogen reductions than a uniform PES policy with cost savings of 8–19%. Moreover, switchgrass has the potential of providing energy supply while reducing greenhouse gases emissions.